Surveillance in America : critical analysis of the FBI, 1920 to the present - Greenberg, Ivan, 1962- (Lexington Books, 2012)
Surveillance in America is a study of FBI surveillance practices and policies since 1920 based on recently declassified FBI files. This wide-ranging study looks at such subjects as the media, academic historians, the Watergate crisis, and surveillance of the American working class.